The American Experience of Integrated Water Resources Management and Its Implications for China - Xue, Hang (International Journal of Natural Resources and Environmental Studies, 2024)
Water, a crucial resource that effectively drives human socio-economic development and ecological conservation, boasts its effectiveness, controllability, and renewability. It is an indispensable strategic resource for social progress. The United States has achieved remarkable results and accumulated valuable experience in integrated water resources management. These encompass integrated watershed planning and governance, efficient water conservancy infrastructure construction, measures to improve ecological environment, wastewater recycling and reuse, water rights management and trading systems, laws, regulations and policy support, water resources monitoring and assessment, and international cooperation and exchanges. These experiences serve as invaluable references for developing countries such as China in enhancing global water management and attaining sustainable development goals. Integrated water resources management gains prominence globally, and the United States has accumulated a wealth of experience and lessons in this area. This article delves into the strategies and accomplishments of integrated water resources management in the U.S., providing China with pertinent inspirations and recommendations.